2005
DOI: 10.1063/1.1935742
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of electromagnetic multichannel data: The signal space separation method

Abstract: Measurement of external magnetic fields provides information on electric current distribution inside an object. For example, in magnetoencephalography modern measurement devices sample the magnetic field produced by the brain in several hundred distinct locations around the head. The signal space separation ͑SSS͒ method creates a fundamental linear basis for all measurable multichannel signal vectors of magnetic origin. The SSS basis is based on the fact that the magnetic field can be expressed as a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
340
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(340 citation statements)
references
References 30 publications
0
340
0
Order By: Relevance
“…More recent investigations showed very similar tendencies. Van der Hiele et al (2007) found negative correlations between theta power and tests of global domain. In addition, negative correlations with tests such as the TMTB or semantic fluency were described by the authors.…”
Section: Discussionmentioning
confidence: 98%
“…More recent investigations showed very similar tendencies. Van der Hiele et al (2007) found negative correlations between theta power and tests of global domain. In addition, negative correlations with tests such as the TMTB or semantic fluency were described by the authors.…”
Section: Discussionmentioning
confidence: 98%
“…The temporal signal space separation (tSSS) and head movement compensation aligning the data to the mean head position were used first (Elekta MaxFilter 2.2) to suppress noise from outside of the MEG dewar and to compensate for effects related to infants' head movement during the recording. This procedure was designed to improve the signal-to-noise ratio of the data by suppressing external interference (i.e., noise from outside of the helmet) without introducing excessive reconstruction noise (50,51). The infant head movement was evaluated by assessing the maximum SD of the center head position across all time points.…”
Section: Resultsmentioning
confidence: 99%
“…External noise was removed from the MEG data using the temporal extension of Signal-Space Separation (tSSS) (Taulu and Kajola 2005) as implemented with the MaxFilter software (version 2.2, Elekta-Neuromag) with a 10-s raw data buffer and a subspace correlation limit of 0.9. Data was subsequently adjusted for head movement every 200 ms and transformed into a common space.…”
Section: Meg Recordings and Preprocessingmentioning
confidence: 99%